Effects of different levels of Moringa (Moringa oleifera) seed flour on quality attributes of beef burgers. Issue 1 (2nd January 2016) - Al-Juhaimi, Fahad; Ghafoor, Kashif; Hawashin, Majed D.; Alsawmahi, Omer N.; Babiker, Elfadil E.
Abstract : Meat of beef patties was partially replaced by different levels (0, 2, 4 and 6%) of Moringa seed flour (MSF). The replacement of meat did not significantly ( p ≤ 0.05) affect the chemical composition of the patties. The cooking properties of the patties formulated with MSF improved with the flour level. The thiobarbituric acid value was higher for non-formulated patties than for formulated ones after storage. The addition of MSF slightly reduced the pH of raw patties with the storage time. Patties formulated with MSF had significantly ( p ≤ 0.05) lower aerobic plate counts throughout the storage period. As the level of MSF increased, the patties had high lightness ( L* ) and yellowness ( b* ) values but low redness ( a *) values. A relatively low sensory acceptability was noted for MSF-formulated patties and was slightly reduced at longer storage times, but that of non-formulated ones decreased significantly ( p ≤ 0.05) at longer storage times. The results indicated that M. oleifera seed flour has a high potential as a binder for use in beef patty production in addition to its health and nutritional benefits.